Implementation Of Environmental Administrative Law Enforcement Related To Environmental Approval And License For Environmental Protection And Management Of Palm Oil Factories In The Province Of North Sumatra - Rizky, Fajar Khaify; Safnul, Dody; Meher, Montayana (Faculty of Law, Universitas Pekalongan, 2024)
Palm oil mills have become an integral part of the economy in North Sumatra Province, but the growth of this industry often has negative impacts on the environment. In this context, the implementation of environmental administration law enforcement is very important to ensure sustainable environmental protection and management. This research aims to analyze the implementation of environmental administrative law enforcement related to environmental approvals and permits for palm oil mills in North Sumatra Province. Through a qualitative approach and case studies, data was collected from various sources, including legal documents, government policies, and interviews with relevant stakeholders. The research results show that although there are strict regulations and regulations regarding environmental approvals and permits for palm oil mills, the implementation of environmental administrative law enforcement still faces challenges. Factors such as a lack of human resources, the inability of institutions to supervise effectively, and local political interference are the main obstacles to implementing effective law enforcement. However, this research also found several positive initiatives, such as increasing environmental awareness among the palm oil industry and efforts to strengthen the capacity of environmental law enforcement agencies. The resulting recommendations include expanding trained human resources, increasing transparency in the licensing process, and strengthening cooperation between government, industry, and civil society to achieve sustainable environmental management in North Sumatra Province.